2014
DOI: 10.1149/2.063404jes
|View full text |Cite
|
Sign up to set email alerts
|

pH Effect on Sulfur-Induced Passivity Degradation of Alloy 800 in Simulated Crevice Chemistries

Abstract: The effects of pH on sulfur-induced passivity degradation of Alloy 800 in simulated crevice chemistries were evaluated using electrochemical impedance spectroscopy (EIS), secondary ion mass spectroscopy (SIMS), and Mott-Schottky analysis methods. Experimental results reveal that the detrimental effect of impurities containing sulfur at the reduced or intermediate oxidation level (S x ) on the passivity of Alloy 800 depends significantly on the solution pH. In neutral crevice (NC) chemistry containing chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…1 and 2 with Figs. 3 and 4, it is concluded that the dissolution of metal ions is not remarkable in thiosulfate-free solution, whereas the dissolution of metal ions is significant in thiosulfate-containing solution, which is due to thiosulfate-enhanced anodic dissolution within the pits, and this is consistent with the previous experimental observations [19,23]. Moreover, the current in thiosulfate-containing solution is significantly higher than that in thiosulfate-free solution.…”
Section: Methodssupporting
confidence: 86%
“…1 and 2 with Figs. 3 and 4, it is concluded that the dissolution of metal ions is not remarkable in thiosulfate-free solution, whereas the dissolution of metal ions is significant in thiosulfate-containing solution, which is due to thiosulfate-enhanced anodic dissolution within the pits, and this is consistent with the previous experimental observations [19,23]. Moreover, the current in thiosulfate-containing solution is significantly higher than that in thiosulfate-free solution.…”
Section: Methodssupporting
confidence: 86%
“…30 The initiation of SCC in sensitized Alloy 600 in aqueous Na 2 S 2 O 3 is much lower than that in Na 2 S 4 O 6 solutions, indication that S 2 O 3 2¹ is more detrimental to materials than S 4 O 6 2¹ . 6 Our previous work 31 found that the detrimental effect of impurities containing sulfur at the reduced or intermediate oxidation level on the passivity of Alloy 800 depends significantly on the solution pH.…”
Section: ¹mentioning
confidence: 99%
“…Some electrochemical methods such as open circuit potential (OCP) measurement, linear polarization resistance, electrochemical noise (EN), electrochemical impedance spectroscopy (EIS) are widely used for the purpose mentioned above, because these techniques are based on the mechanism of corrosion, and the measurement system is relatively simple, and easy to operate. [1][2][3][4] Among these techniques, EN has gradually become a promising tool for corrosion measurement. 5 Spontaneous fluctuations of electrode potential and current in an electrochemical system are known as EN.…”
Section: Introductionmentioning
confidence: 99%